2018
DOI: 10.1016/j.ceramint.2018.07.216
|View full text |Cite
|
Sign up to set email alerts
|

CO2 binding capacity of alkali-activated fly ash and slag pastes

Abstract: Quantification of the CO2 binding capacity of reinforced concrete is of high importance for predicting the carbonation potential and service life of these structures. Such information is still not available for alkali activated materials that have received extensive attention as a sustainable substitute for ordinary Portland cement (OPC)-based concrete. To address this gap, this paper evaluates the CO2 binding capacity of ground powders of alkali activated fly ash (FA) and ground granulated blast furnace slag … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…Beside alkalis (Na), calcium ions may also contribute to maintaining a high pH of the pore solution. This is supported by the authors' previous study [37], where it was shown that not all the CaO was consumed by carbonation of studied alkali activated pastes. This implies that, after NaOH carbonation, the remaining CaO can act as a buffering agent for the pH of the pore solution.…”
Section: Alkali Losssupporting
confidence: 85%
“…Beside alkalis (Na), calcium ions may also contribute to maintaining a high pH of the pore solution. This is supported by the authors' previous study [37], where it was shown that not all the CaO was consumed by carbonation of studied alkali activated pastes. This implies that, after NaOH carbonation, the remaining CaO can act as a buffering agent for the pH of the pore solution.…”
Section: Alkali Losssupporting
confidence: 85%
“…The reason is that unlike OPC, AAC has no portlandite [30], so the carbonate process is affected by various factors. To date, the carbonation of AAC has been associated with the pH reduction of the pore solution, the precipitation of Na-rich carbonates and the decalcification of Ca-rich phases (C-S-H gel) [56,57]. The CaCO 3 , which is formed as a result of carbonation, is classified into crystalline phases and an amorphous phase [57].…”
Section: Resultsmentioning
confidence: 99%
“…To date, the carbonation of AAC has been associated with the pH reduction of the pore solution, the precipitation of Na-rich carbonates and the decalcification of Ca-rich phases (C-S-H gel) [56,57]. The CaCO 3 , which is formed as a result of carbonation, is classified into crystalline phases and an amorphous phase [57]. Therefore, CaCO 3 , which is distinguished by calcite, vaterite and aragonite, may be different from XRD and TG/DTG [57].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This weight loss is likely due to the decomposition of amorphous calcium carbonate (CaCO 3 ∙xH 2 O [36]) rather than vaterite, which is because the peaks for vaterite was not detected in the XRD result as shown in Figure 5f. Amorphous CaCO 3 was reportedly decomposed at temperatures between 245 °C and 645 °C [37].…”
Section: Resultsmentioning
confidence: 99%